Potential Impact of Non-conventional Protein Resources Cyamopsis tetragonoloba (Guar Meal) in Lamb’s Diet - Ali Mahdi Mahmood MANI (Acta Veterinaria Eurasia)
The objective of this study was to evaluate the effect of using non-conventional protein sources of plant origin (guar meal) as a promising strategy for improving feed efficiency in Awassi sheep. This study included: (i) investigation of the nutrient intake and productive performance of lambs, (ii) appraisal nutrients digestibility and ruminal parameters (pH, N-H3 and volatile fatty acids), where experiment 1 used 18 Awassi lambs (age 2.5-3 months) distributed and assigned into three groups (randomly), and experiment 2 used nine lambs in randomized block design with three replicates. Three experimental concentrate diets were formulated to be isonitrogen (crud protein [CP] content 15.6%) and isoenergy (metabolic energy [ME] content 2.4 Mcal/kg). The results showed that the final body weight and dry matter intake (kg/day and g/kg of body weight) were not significantly affected (p=.05) despite the improvements occurring. In addition, the guar meal significance increased (p ≤ .05) of average daily gain than total weight compared to the other experimental diets. The guar meal affected NH3 concentration (p=.037), total volatile fatty acids (TVFAs) (p=.001), and molar proportions of acetate and propionate (p=.027). The molar proportions of valerate (p < .05) and caproate (p < .05) were significantly reduced when replacing traditional sources of protein. No difference (p > .05) in the dry matter, ether extract, and crude protein digestibility was observed among the three diets. In conclusion, guar meal could replace traditional conventional protein sources in ruminant diets with no adverse effects on feed intake, or digestibility.